Drug release of electrohydrodynamic spray coated polymers - Lin, Caryn Xingzhi. (2009)
The study of controlled drug release of biodegradable Poly(L-lactide) films using a novel technique Electrohydrodynamic Atomization, to spray coat the film with lidocaine base, was reported in this report. The main objectives of this project are to electrospray lidocaine on Poly(L-lactide) film to produce micro to nano-sized surface features and to study the rate of controlled drug release in vitro. SEM results have shown that Electrohydrodynamic Atomization of lidocaine solution forms micron-sized craters on the surface of Poly(L-lactide) film. This surface modification roughens the surface, which probably promotes cell adhesion that is useful for implants and tissue engineering applications. On average, each micron-sized crater was measure to be approximately 78mm. Theoretically, the amount of lidocaine electrosprayed on Poly(L-lactide) film of dimension 2×2cm is 0.07wt%. TGA results shows no difference in decomposition temperature when both Poly(L-lactide) film and lidocaine-loaded Poly(L-lactide) film underwent thermal ramping. Similarly, FTIR yielded no characteristic peak for lidocaine as well. Lidocaine drug release was studied at predetermined time intervals. However, the low wt% of drug released is considered negligible. Nevertheless, Electrohydrodynamic Atomization is an effective micron-fabrication technique to coat drugs in a monodisperse fashion.